Culture of Food Preservation among Bushehrian People in Iran - Ravanipour, Maryam; Ravanipour, Masoumeh; Pouladi, Shahnaz; Vahedparast, Hakimeh; Yazdankhahfard, Mohammadreza; Hajinejad, Fatemeh; Abedi, Heidarali (Pakistan Journal of Nutrition, 2009)
The correlation between food and health has been documented through many studies. Cultures have a fundamental role in the process of food selection, preparation and storage methods. It is important that health professionals and nutritionists develop a cultural awareness and use resources targeted toward a specific group. Because the main goal of this study was to find a description of cultural structures of food preservation among Bushehrian people, we used a qualitative method of research which deals with direct description of a group, culture or community-Ethnography-among Bushehrian people. Four main categories were emerged from the findings: 1) foods tendency of the families, 2) economic-environment point of view, 3) paradox between tradition and technology and 4) believes about the foods. Health considerations were placed in the core of all categories. So, it can be the main point of attentions for interventions for health care professionals.